Physical exercise as a friend not a foe in acute kidney diseases through immune system modulation - Costanti-Nascimento, Ana Carolina; Brelaz-Abreu, Leonilia; Bragança-Jardim, Elayne; Pereira, Welbert de Oliveira; Camara, Niels Olsen Saraiva; Amano, Mariane Tami (Frontiers in Immunology, 2023)
Regular and moderate exercise is being used for therapeutic purposes in treating several diseases, including cancer, cardiovascular diseases, arthritis, and even chronic kidney diseases (CKDs). Conversely, extenuating physical exercise has long been pointed out as one of the sources of acute kidney injury (AKI) due to its severe impact on the body’s physiology. AKI development is associated with increased tubular necrosis, which initiates a cascade of inflammatory responses. The latter involves cytokine production, immune cell (macrophages, lymphocytes, and neutrophils, among others) activation, and increased oxidative stress. AKI can induce prolonged fibrosis stimulation, leading to CKD development. The need for therapeutic alternative treatments for AKI is still a relevant issue. In this context arises the question as to whether moderate, not extenuating, exercise could, on some level, prevent AKI. Several studies have shown that moderate exercise can help reduce tissue damage and increase the functional recovery of the kidneys after an acute injury. In particular, the immune system can be modulated by exercise, leading to a better recovery from different pathologies. In this review, we aimed to explore the role of exercise not as a trigger of AKI, but as a modulator of the inflammatory/immune system in the prevention or recovery from AKI in different scenarios. In AKI induced by ischemia and reperfusion, sepsis, diabetes, antibiotics, or chemotherapy, regular and/or moderate exercise could modulate the immune system toward a more regulatory immune response, presenting, in general, an anti-inflammatory profile. Exercise was shown to diminish oxidative stress, inflammatory markers (caspase-3, lactate dehydrogenase, and nitric oxide), inflammatory cytokines (interleukin (IL)-1b, IL-6, IL-8, and tumor necrosis factor-α (TNF-α)), modulate lymphocytes to an immune suppressive phenotype, and decrease tumor necrosis factor-β (TGF-β), a cytokine associated with fibrosis development. Thus, it creates an AKI recovery environment with less tissue damage, hypoxia, apoptosis, or fibrosis. In conclusion, the practice of regular moderate physical exercise has an impact on the immune system, favoring a regulatory and anti-inflammatory profile that prevents the occurrence of AKI and/or assists in the recovery from AKI. Moderate exercise should be considered for patients with AKI as a complementary therapy.